Facing Severance - Bal, Mieke (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
In the face of the current wave of mass migration in Western Europe, we ignore one group of people affected by the departure of young people from their communities: their mothers. Not only had they seen their children leave, but they even had to support that decision — “it's for his good” — while it affected their lives with a deep loss. This prompted the author to develop a video pro ject in which the heretofore invisible mothers were given the opportunity to speak about their departed children. The installation is entirely devoted to the issue of facing: literally, indirectly, and figuratively. The aesthetic of close-up, of one- shot filming, no-editing and hence, of non-interventionism, and of intimacy in filming as well as projecting makes this politics of facing a viable alternative to what Luc Boltanski has termed “the politics of pity.” In this article the author develops the concept of this project, both philosophically and semiotically, with the help of Spinoza and Deleuze, in order to articulate in what way this is an instance of “migratory aesthetics” as political art.